24-hour movement behaviors and changes in quality of life over time among community-dwelling older adults: a compositional data analysis - Lotta Palmberg; Kristin Suorsa; Antti Löppönen; Laura Karavirta; Taina Rantanen; Timo Rantalainen (BMC, 2024)
Abstract Background Favorable movement behavior patterns, comprising more physical activity, less sedentary behavior, and sufficient sleep, may promote the maintenance of good quality of life (QoL) with advancing age. The aim of the present study was to investigate whether movement behaviors predict future changes in QoL among community-dwelling older adults over a four-year follow-up. Methods Participants were 75-, 80- and 85-year-old community-dwelling older adults (n = 203) followed up for 4 years. Participants wore thigh- and trunk-mounted accelerometers for 3-7 days at baseline. Proportion of time-use in physical activity, standing and sedentary behavior were assessed based on body posture and movement intensity. Time in bed was determined using an automated algorithm. QoL was assessed during a home interview using the short Older People's Quality of Life Questionnaire at baseline and follow-up (range 13-65, higher scores indicate higher QoL). Compositional linear regression analysis was used to study whether baseline time-use composition predicts changes in QoL. Results Over the 4-year follow-up, QoL scores decreased by 5% on average. Higher physical activity in relation to the other movement behaviors was associated with increase in QoL over time (βilr 0.94, p = 0.013), but this association attenuated after adding baseline physical function into the model. Sedentary behavior, standing, and time in bed were not associated with changes in QoL. Theoretical reallocation of 30 min of physical activity into sedentary behavior, standing or time in bed was estimated to decrease QoL by 0.5 (CI 95% -0.6 to -0.4), 0.6 (-0.7 to -0.5) and 0.4 (-0.5 to -0.3) points, respectively. Conclusions Theoretical reallocation of physical activity into sedentary behavior, standing, and time in bed was found to be associated with prospective decline in QoL among older adults. Engaging more in physical activity and less in more passive activities may promote better QoL with advancing age.